2019
DOI: 10.1002/eji.201848024
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of lipoteichoic acid from Lactobacillus rhamnosus GG overcomes UVB‐induced immunosuppression and impairs skin tumor growth in mice

Abstract: There is increasing evidence of the relevant connection and regulation between the gut and skin immune axis. In fact, oral administration of lipoteichoic acid (LTA) from Lactobacillus rhamnosus GG (LGG) prevents the development of UV-induced skin tumors in chronically exposed mice. Here we aim to evaluate whether this LTA is able to revert UV-induced immunosuppression as a mechanism involved in its anti-tumor effect and whether it has an immunotherapeutic effect against cutaneous squamous cell carcinoma. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…On the other hand, changes in the intestinal microbiota and intake of probiotics can affect the immune response of the skin. In fact, lipoteichoic acid (LTA) from LGG ( Lactobacillus rhamnosus ) can prevent skin tumors in mice exposed to long-term ultraviolet rays ( Friedrich et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, changes in the intestinal microbiota and intake of probiotics can affect the immune response of the skin. In fact, lipoteichoic acid (LTA) from LGG ( Lactobacillus rhamnosus ) can prevent skin tumors in mice exposed to long-term ultraviolet rays ( Friedrich et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specific strains of lactic acid bacteria may have a beneficial influence on the composition and metabolism of the intestinal microbiota and in some cases have been reported to inhibit the growth of enteropathogenic bacteria [ 72 ]. Many studies have shown a connection between the intestinal immune axis and the skin [ 74 ] and consumption of food containing probiotics was shown to improve skin health, maintaining skin homeostasis and regulating the cutaneous immune system [ 49 ].…”
Section: Photoprotectionmentioning
confidence: 99%
“…In the same way, the administration of a probiotic strain of Lactobacillus rhamnosus GG (LGG) was demonstrated to prevent the development of skin tumors thanks to the activity of its lipoteichoic acid (LTA), a component of the Gram-positive bacteria cell wall. In a murine model, LTA decreased UV-induced skin immunosuppression and thus significantly reduced UV-induced skin tumor growth [ 74 ]. Other photoprotective candidates can be considered, such as Lactobacillus plantarum HY7714, Bifidobacterium breve and Bifidobacterium longum [ 75 , 77 , 78 ].…”
Section: Photoprotectionmentioning
confidence: 99%
“…lipoteichoic acid produced a reduction in squamous cell carcinomas in chronically UV-exposed mice, reinforcing Th1 response ( Weill et al, 2013 ). Moreover, this treatment was also effective in preventing UV-induced immunosuppression ( Friedrich et al, 2019 ). In addition, the oral treatment with Bifidobacterium spp.…”
Section: Mechanism Of Action Of Probioticsmentioning
confidence: 99%